Determination of cinnamic acid in human urine by differential-pulse polarography - Ferreira, V. S.; Melios, C. B.; Zanoni, Maria Valnice Boldrin [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Royal Soc Chemistry, 1996)
The differential pulse polarographic behaviour of cinnamic acid was studied in acetate and phosphate buffer solutions (pH 3.5-7.5). The reduction mechanism is discussed. The drug can be determined at pH 5.0 over the concentration range 5 X 10(-5)-1 X 10(-3) mol l(-1). The effect of tetraalkylammonium salts on the electroanalytical determination of cinnamic acid was investigated, the direct determination of the drug (0.7-5.5 mu g ml(-1)) in urine samples diluted with acetate buffer (pH 5.0) can be effected in the presence of 1 x 10(-3) mol l(-1) cetyldimethylethylammonium bromide solution. The detection limit was found to be 0.1 mu g ml(-1). The relative standard deviation from six determinations at the 5.5 mu g ml(-1) level was 1%.
Keywords: cinnamic acid; polarographic determination; differential-pulse polarography; urine